The Decadal Evolution of Career Decision-Making (2015–2025): A Bibliometric Mapping of Emerging Frontiers - Noviati, Nur Pratiwi; Kadiyono, Anissa Lestari; Sulastiana, Marina; Lubis, Fitriani Yustikasari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: As the modern workplace undergoes systemic shifts, the literature on career decision-making (CDM) has expanded in volume but fragmented in focus. This study synthesizes 1,872 Scopus-indexed articles from 2015 to 2025 to map the field’s intellectual landscape and emerging trajectories. Utilizing performance analysis and science mapping, we identify an exponential growth in productivity, peaking in 2025, with the United States and Itamar Gati maintaining dominant citation influence. While Social Cognitive Career Theory remains the primary bedrock, keyword co-occurrence and overlay visualizations reveal a significant paradigm shift: research is pivoting from isolated individual-psychological factors toward highly contextual, adaptive, and systemic models. Furthermore, international co-authorship patterns indicate a burgeoning diversification of global perspectives beyond Western-centric frameworks. These findings provide a strategic roadmap for scholars, highlighting the transition from "symptom-based" CDM research to "context-adaptive" modeling in an era of global labor market disruption. Keywords: bibliometric analysis, career decision-making,